The effect of EU ETS allowances on electricity prices : How do emission allowances impact electricity prices in Finland during the IV phase of the ETS? - Laine, Julius (My University, 2026)
The purpose of this master’s thesis is to analyse how emission allowances impact electricity prices in Finland during the fourth phase of the European Union Emissions Trading System (EU ETS). The topic is highly relevant, as the emissions trading system plays a central role in the European Union’s climate policy and is a key instrument in combating climate change. In addition, the stability of the energy system and energy security have become increasingly important issues in Europe, particularly following Russia’s invasion of Ukraine and the current tensions in the Middle East. The research hypothesis of this thesis is that emission allowances have a positive impact on electricity prices in Finland. The relationship between emission allowances and electricity prices during the fourth phase of the emissions trading system has been studied relatively little compared to earlier phases, especially in the Finnish context. This thesis contributes to addressing this research gap. The dataset consists of daily data from the period 1 January 2021 to 30 September 2025, covering the current fourth phase of the EU ETS. To evaluate the impact of emission allowances, multiple linear regression analyses were conducted, controlling for other factors affecting electricity price formation, such as energy sources used in electricity generation, fuel prices, weather variables, electricity demand, interest rates, and cross-border electricity transmission. The key results of the multiple linear regression analyses indicate that the effect of emission allowance prices on electricity prices in Finland is positive and statistically significant, and the control variables largely behave as expected. The results confirm and support previous literature suggesting that emission allowance prices have a positive effect on electricity prices, with cost pass-through rates ranging between 60% and 100%. The findings of this thesis and the existing literature are significant, as they have implications for policymakers, consumers, and the broader economy. Although the share of carbon-intensive electricity generation is relatively small in Finland’s total electricity production, it still affects electricity prices. Higher electricity prices weaken households’ purchasing power, increase firms’ production costs, and thereby negatively impact the overall economy. The effects impact households with low electricity consumption especially hard, as they face the highest electricity prices. The results suggest that reducing the use of carbon-intensive energy sources in electricity generation could lower electricity prices, improve the stability and energy security of Finland’s energy system, and support Finland’s goal of achieving carbon neutrality.

Tämän pro gradu -tutkielman tarkoituksena on analysoida, miten päästöoikeudet vaikuttavat sähkön hintoihin Suomessa Euroopan unionin päästökauppajärjestelmän neljännen vaiheen aikana. Aihe on erittäin ajankohtainen, sillä päästökauppajärjestelmä on keskeisessä asemassa Euroopan unionin ilmastopolitiikassa ja sitä käytetään ilmastonmuutoksen torjunnassa. Lisäksi energiajärjestelmän vakaus ja energiaturvallisuus ovat nousseet yhä tärkeämmiksi aiheiksi Euroopassa erityisesti Venäjän hyökkäyssodan Ukrainaan sekä Lähi-idän nykyisten jännitteiden jälkeen. Tämän tutkielman tutkimushypoteesina on, että päästöoikeuksilla on positiivinen vaikutus Suomen sähköhintoihin. Päästöoikeuksien ja sähköhintojen suhdetta päästökauppajärjestelmän neljännessä vaiheessa on tutkittu melko vähän verrattuna aikaisempiin vaiheisiin erityisesti Suomessa. Tämä tutkielma vastaa osaltaan tähän tutkimusaukkoon. Tutkimusaineisto koostuu päivittäisestä datasta ajanjaksolta 1.1.2021–30.9.2025, joka kattaa Euroopan unionin päästökauppajärjestelmän nykyisen neljännen vaiheen. Päästöoikeuksien vaikutuksen arvioimiseksi suoritettiin useita lineaarisia regressioanalyysejä, joissa kontrolloitiin samalla muita sähkön hinnanmuodostukseen vaikuttavia tekijöitä, kuten sähköntuotannon energialähteitä, polttoaineiden hintoja, säämuuttujia, sähkön kysyntää, korkotasoja sekä rajat ylittäviä sähkönsiirtoja. Moninkertaisten lineaaristen regressioanalyysien keskeiset tulokset osoittivat, että päästöoikeuksien hintojen vaikutus Suomen sähkön hintoihin oli positiivinen ja tilastollisesti merkitsevä, ja kontrollimuuttujat käyttäytyivät suurilta osin odotetulla tavalla. Tulokset vahvistavat ja tukevat aiempaa kirjallisuutta siitä, että päästöoikeuksien hinnat vaikuttavat sähkön hintoihin positiivisesti ja että kustannusten siirtymisaste vaihtelee 60–100 prosentin välillä. Tutkielman tulokset ja aiempi kirjallisuus ovat merkittäviä, koska ne vaikuttavat niin päätöksentekijöihin, kuluttajiin kuin koko talouteen. Vaikka hiili-intensiivisen sähköntuotannon osuus on hyvin pieni Suomen sähkön kokonaistuotannosta, sillä on silti vaikutusta sähkön hintoihin. Korkeammat sähkön hinnat heikentävät kotitalouksien ostovoimaa, kallistavat yritysten tuotantokustannuksia ja vaikuttavat tätä kautta negatiivisesti koko talouteen. Erityisesti vaikutukset kohdistuvat kotitalouksiin, joiden sähkönkulutus on vähäistä, sillä heidän maksamansa sähkön hinta on korkein. Tulokset viittaavat siihen, että hiili-intensiivisten energialähteiden käytön vähentäminen sähköntuotannossa voisi alentaa sähkön hintoja, parantaa Suomen energiajärjestelmän vakautta ja energiaturvallisuutta sekä edistää Suomen tavoitetta saavuttaa hiilineutraalisuus.
Keywords: emission trade; emissions; prices; European Union countries; emission allowances; electricity; markets (systems); climate policy; electricity market; integration (passive); fi=Taloustiede|en=Economics|; fi=Taloustieteen maisteriohjelma|en=Master's Programme in Economics|